Disruption of the Atlantic Meridional Circulation during Deglacial Climates Inferred from Planktonic Foraminiferal Shell Weights - Stergios D. Zarkogiannis (Journal of Marine Science and Engineering, 2021)
Changes in the density structure of the upper oceanic water masses are an important forcing of changes in the Atlantic Meridional Overturning Circulation (AMOC), which is believed to widely affect Earth’s climate. However, very little is known about past changes in the density structure of the Atlantic Ocean, despite being extensively studied. The physical controls on planktonic foraminifera calcification are explored here, to obtain a first-order approximation of the horizontal density gradient in the eastern Atlantic during the last 200,000 years. Published records of Globigerina bulloides shells from the North and Tropical eastern Atlantic were complemented by the analysis of a South Atlantic core. The masses of the same species shells from three different dissolution assessed sediment cores along the eastern Atlantic Ocean were converted to seawater density values using a calibration equation. Foraminifera, as planktonic organisms, are subject to the physical properties of the seawater and thus their shells are sensitive to buoyancy forcing through surface temperature and salinity perturbations. By using planktonic foraminifera shell weight as an upper ocean density proxy, two intervals of convergence of the shell masses are identified during cold intervals of the last two deglaciations that may be interpreted as weak ocean density gradients, indicating nearly or completely eliminated meridional circulation, while interhemispheric Atlantic density differences appear to alleviate with the onset of the last interglacial. The results confirm the significance of variations in the density of Atlantic surface waters for meridional circulation changes.